Energy characteristic of a processor allocator and a Network-on-Chip - Zydek, Dawid; Selvaraj, Henry; Borowik, Grzegorz; Łuba, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
Energy consumption in a ChipMultiProcessor (CMP) is one of the most important costs. It is related to design aspects such as thermal and power constrains. Besides efficient on-chip processing elements, a well-designed Processor Allocator (PA) and a Network-on-Chip (NoC) are also important factors in the energy budget of novel CMPs. In this paper, the authors propose an energy model for NoCs with 2D-mesh and 2D-torus topologies. All important NoC architectures are described and discussed. Energy estimation is presented for PAs.
Keywords: CMP; PA; energy model; processor allocation